Generalized quotients and holographic duals for 5d S-fold SCFTs - Apruzzi, F; Bergman, O; Kim, H-C; Uhlemann, CF (Springer, 2023)
ℤn S-folds of 5d SCFTs, including TN, which lead to brane webs with E6,7,8 7-branes were discussed recently in [1, 2]. We generalize the construction to ‘fractional quotients’, which are based on ℤn actions linking multiple copies of the seed theory and lead to H0,1,2 7-branes. We provide the holographic duals for both classes. This expands the space of explicitly known Type IIB AdS6 solutions by incorporating F-theory 7-branes of type E6,7,8 and H0,1,2, extending previous constructions for O7-planes. We discuss observables including the free energies and link the results to matrix model descriptions.